Troubleshooting Electronic Circuits : A Guide to Learning Analog Electronics - Quan, Ronald (McGraw-Hill's AccessEngineering., 2020)
Debug, Tweak and fine-tune your DIY electronics projects. This hands-on guide shows, step by step, how to build, debug, and troubleshoot a wide range of analog electronic circuits. Written by electronics guru Ronald Quan, Troubleshooting Electronic Circuits: A Guide to Learning Analog Circuits clearly explains proper debugging techniques as well as testing and modifying methods. In multiple chapters, poorly-conceived circuits are analyzed and improved. Inside, you will discover how to design or re-design high-quality circuits that are repeatable and manufacturable.